2018
DOI: 10.1016/j.ebiom.2017.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Ancestral Variations of the PCDHG Gene Cluster Predispose to Dyslexia in a Multiplex Family

Abstract: Dyslexia is a heritable neurodevelopmental disorder characterized by difficulties in reading and writing. In this study, we describe the identification of a set of 17 polymorphisms located across 1.9 Mb region on chromosome 5q31.3, encompassing genes of the PCDHG cluster, TAF7, PCDH1 and ARHGAP26, dominantly inherited with dyslexia in a multi-incident family. Strikingly, the non-risk form of seven variations of the PCDHG cluster, are preponderant in the human lineage, while risk alleles are ancestral and conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…Members of the cadherin superfamily have emerged as key contributors to neurodevelopmental disorders, including autism, schizophrenia, bipolar disease, and intellectual disability (60)(61)(62). We have shown that Dscam can regulate the function of cadherins and protocadherins, making it a candidate target for these disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…Members of the cadherin superfamily have emerged as key contributors to neurodevelopmental disorders, including autism, schizophrenia, bipolar disease, and intellectual disability (60)(61)(62). We have shown that Dscam can regulate the function of cadherins and protocadherins, making it a candidate target for these disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…They mediate a variety of processes, including neuronal survival, morphogenesis and connectivity, synaptic maintenance, and spatial patterning of axons and dendrites [86]. The variants in PCDH genes have been reported to be associated with dyslexia and bipolar disorder [87, 88].…”
Section: Discussionmentioning
confidence: 99%
“…All identified variants clustered in the variable 5′ exons, which encode for the extracellular protocadherin domain. Protocadherins are predominantly expressed in the developing human brain and are known to play a role in neuronal connectivity, thus ensuring formation and maintenance of neural circuits [ 70 ].…”
Section: Exploring Genetic Susceptibility To Sld—the Early Timesmentioning
confidence: 99%